2011
DOI: 10.1096/fasebj.25.1_supplement.938.2
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics of Aiptasia pallida and Symbiodinium: a model system for investigating the molecular basis of coral symbiosis

Abstract: Changing oceanic environmental factors disrupt the symbiotic relationship between cnidarians and a photosynthetic dinoflagellate symbiont, leading to expulsion of the symbiont from the cnidarian and endangering fragile coral ecosystems. The symbiosis between the anemone Aiptasia pallida and Symbiodinium is a model system for studying the molecular changes that occur during the establishment, maintenance and disruption of symbiosis. The symbiont resides in a specialized membrane component called the symbiosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Membrane lipid molecular species were analyzed in two symbiotic tropical hydrocorals, Millepora dichotoma and M. platyphylla , and the asymbiotic cold-water hydrocoral Allopora stejnegeri [ 48 , 49 ]. The sea anemone Aiptasia pallida [ 50 , 51 ] and the zoantharian Palythoa tuberculosa [ 38 ] were also subjected to analyses of glycerophospholipid molecular species ( Table 1 ).…”
Section: Coral Host Lipidomementioning
confidence: 99%
See 1 more Smart Citation
“…Membrane lipid molecular species were analyzed in two symbiotic tropical hydrocorals, Millepora dichotoma and M. platyphylla , and the asymbiotic cold-water hydrocoral Allopora stejnegeri [ 48 , 49 ]. The sea anemone Aiptasia pallida [ 50 , 51 ] and the zoantharian Palythoa tuberculosa [ 38 ] were also subjected to analyses of glycerophospholipid molecular species ( Table 1 ).…”
Section: Coral Host Lipidomementioning
confidence: 99%
“…Most of them contained 24:5 and 24:6 PUFAs (18:0alk/24:5 and 18:0alk/24:6) which are known to be chemotaxonomic markers of soft corals [ 26 , 64 ]. In corals with a solid exoskeleton ( Acropora , Millepora , and Allopora ), only the diacyl forms of PS were identified (alkylacyl PS forms were in trace amounts) [ 37 , 48 , 50 ]. These PS molecular species contained 22:4, 22:5, and 22:6 PUFAs (18:0/22:4, 20:0/22:4, 18:0/22:5, 20:0/22:5, and 18:0/22:6).…”
Section: Coral Host Lipidomementioning
confidence: 99%
“…In previous studies, scientists have shown that 18:4n and 22:6nare the specific fatty acids for lipid biosynthesis of symbiotic algae of corals [18,21]. However, in the lipids of zooxanthellae, only diacylphospholipids were identified [15,16].…”
Section: Molecular Species Of Pcmentioning
confidence: 99%
“…Most tropical corals contain intracellular symbiotic algae, most of which are unicellular algae of the genus Symbiodiniaceae (referred to as zooxanthellae). These microalgae are essential for the survival of the host corals, and the composition of the total lipids of these species will include both those of the host coral and symbiotic microalgae [15][16][17]. Despite the diverse data on fatty acids and lipid classes, the number of studies focused on molecular species of these invertebrates is still limited, especially in coral species.…”
Section: Introductionmentioning
confidence: 99%
“…These lipidomes have been partly described from some species of shrimp 10 12 , lobsters 13 , crabs 14 , 15 , jellyfish 16 , 17 , starfish 18 , sea urchins 18 , holothurians 18 , bivalves 19 25 , gastropods 26 , nudibranch molluscs 27 , 28 , sponges 29 , and hydrocorals 30 , 31 . Among coral polyps (the class Anthozoa), lipidome or its polar part has been analyzed in some species belonging to four orders: Scleractinia (reef-building corals) 32 34 , Alcyonacea (soft corals) 35 37 , Zoantharia 38 , and Actiniaria (sea anemones) 39 41 . No lipidome data have been obtained for members of other Anthozoa orders such as Gorgonacea, Pennatulacea, Antipatharia, and Ceriantharia.…”
Section: Introductionmentioning
confidence: 99%